PEMBERIAN EDUKASI DINI VAKSINASI COVID 19 DAN EDUKASI PHBS DI SD NEGERI 02 CAMPAGO GUGUK BULEK BUKITTINGGI - Lisa Fradisa; Kalpana Kartika (Universitas Pahlawan Tuanku Tambusai, 2022)
Various efforts to prevent the spread of Covid-19 are still being carried out, including strict enforcement of health protocols, vaccinations, increasing knowledge about personal and environmental health as well as various other actions in breaking the chain of spreading the Covid-19 virus. Vaccination is very important in the formation of herd immunity, which aims to reduce the adverse effects of viral infections that occur. Children are also a group that is vulnerable to Covid 19. Elementary school is an educational setting that has the potential for Covid-19 transmission. SD Negeri 02 Campago Guguak Bulek Bukittinggi, as one of the elementary schools that has implemented face-to-face learning in class. This will certainly be a great opportunity for the spread of the covid 19 virus, if awareness of the importance of complying with health protocols, knowledge of vaccinations and knowledge of clean and healthy living behavior has not been realized properly. Given the importance of early knowledge about covid 19 vaccination, and health education regarding clean and healthy living behavior, the DIII Nursing Study Program, Perintis University also takes part in community service activities with the aim of providing early knowledge about covid 19 vaccination and creating awareness of health care. themselves and the environment, through the theme “Providing Early Education on Covid 19 Vaccination and Health Education on Clean and Healthy Behavior at State Elementary School 02 Campago Guguk Bulek Bukittinggi'. The methods in this activity are providing education through counseling, watching videos and demonstrations. The results of the service show the enthusiasm of students, this can be seen from the number of questions and responses by participants during the discussion of activities. From these results, it can be concluded that this educational activity can increase students' knowledge and awareness of the importance of COVID-19 vaccination as well as personal and environmental hygiene. Keywords: Vaccination, covid-19, Health Education